Rancang Bangun Sistem Informasi Daya Tarik Wisata Berbasis Web (Studi Kasus Dinas Kebudayaan dan Pariwisata Jawa Timur) - Febrian Nanda Pratama; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
One indicator of the success of tourism is a tourism information is complete and accurate. As long as this information details about the East Java tourism only in book form at the Department of culture and tourism (East Java), so that prospective tourists should come at the Department of culture and tourism of East Java, to find out information on excursions in East Java.The solution to the difficulty in knowing no tourist information tour of East Java is the Department of culture and tourism provide tourist information East Java more accessible, so that tourists can be easier in knowing that tourism is going to go. Therefore the web application need to be made, so as to help travelers in East Java tourism information knowing that complete anywhere and anytime. In addition, in the web application there is location information about tourism in East Java by using the Google Maps API as supporters in the display map.